Connect your data to Power BI - Williams, Chennel (O'Reilly Media, Inc., 2024)
This video series is all about learning to use Power BI, a Microsoft tool that helps you to turn data into valuable insights. Whether you've never used it, or have played around with it a bit, these videos will help you step by step, from the very basics of getting your data into Power BI, to making cool charts and dashboards you can share with others. The goal is to make you good at using Power BI to identify and visualize important insights from your data. Why Power BI? Well, nowadays, businesses have tons of data, and they need people who can make sense of it. That's where Power BI comes in-it lets you see the story your data is telling, which helps businesses make smarter decisions. This video series tackles a big problem: lots of data, but not enough knowledge on how to use it within the organization. By the end, you'll not only get the hang of Power BI's tools and tricks but also learn how to present your data findings in a way that's easy for everyone to understand, making you a valuable asset in any job that deals with data.
Online resource; title from title details screen (O'Reilly, viewed July 9, 2024)
Keywords: Microsoft Power BI (Computer file); Information visualization -- Computer programs; Business intelligence -- Computer programs; Business -- Data processing; Visualisation de l'information; Logiciels; Gestion; Informatique; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet